UPAYA MENINGKATKAN KEMAMPUAN GURU AGAMA HINDU DALAM MENGGUNAKAN ALAT PERAGA SEBAGAI MEDIA PEMBELAJARAN MELALUI FOCUS GROUP DISCUSSION (FGD) - Ida Bagus Suparta (Pascasarjana Universitas Hindu Indonesia, 2017)
The problem which has made the quality of student understanding and reasoning to be in the lower standard in responding the lessons given by the teachers is because the teachers are disable and unwilling to create, manage, and apply the props. Based on this problem, this research has been conducted with the aim to increase the ability of Hindu religion teachers in the District of Tampaksiring in creating and managing as well as using the props as their medium of learning through Focus Group Discussion (FGD).